PENINGKATAN KETERAMPILAN PRODUKSI DAN FINISHING PRODUK KERAMIK HIAS DAN SOUVENIR MAHASISWA PROGRAM STUDI PENDIDIKAN SENI RUPA DI INDUSTRI KEM:MIKTUNAS ASRI - Kasiyan, Kasiyan (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
Program   intention   of   this   activity,    which   named      job   trammg.  on~:::rrepreneurship,is giving the partical experience stock in the form of knowledge,skill, also motivation  and attitude  objectively, to  all  student as participant while aving a job training, doing together-the performance totally in the field of ceramic decorated industry.Further is also expected, that the participant will be able to apply the values of entrepreneurship, to be a benefit to the student after finishing their lecture in a period to coming.                                                                                      -Method and execition pattern used in this job training's  activity is, within the theory of stock purchasing, conception about entrepreneurship, and the management of medium small enterprise, and also direct pratice in industry.,          Result of this activity execution is inferential as follows. All of the participant from this job training on entrepreneurship have done the following activities. a) Stock phase in purchasing  which located in campus; b) Practising  of preproduce phase directly, in the from of ceramic raw material processing, namely clay; c) Practising the production, which consists of these activities : design making, making of product printing;  mould,  ceramic  products  making  by  various  techniques,  practising  in draining and  will  product,  and  also  finishing  product  by various  techniques,  d) Practice or application   the experince on postproduction   phase, which consists as follow; study of the warehousing,  naking of packing product, and management of show room; and e) The study of managing an enterprise and making of new proposal which aims to effort a new enterprise.Key words:   training,  production,  and finishing ceramic.